(untitled) (Indian Journal of Nematology, 2024)
A survey was under taken to find out the status of nematode problems associated with pigeonpea grown in Bendelkhnad region of Uttar Pradesh. Thirteen nematode genera were observed in the soil samples collected from pigeonpea fields. Nematode genera observed were Hoplolaimus, Tylenchorhynchus, Helicotylenchus, Tylenchus, Heterodera cajani, Pratylenchus, Basiria, Aphelenchus, Meloidogyne, Filenchus, Boleodorus, Rotylenchulus and Scutellonema. Hoplolaimus was most prominent nematode genera observed with Prominence value (PV) of 190.8, Absolute frequency of 69.0% and absolute density 229.7 nematodes/100 cc soil. This was followed by Tylenchorhynchus and Tylenchus. Juveniles of H. cajani were observed in 33% of the fields surveyed. H. cajani cysts were observed in 50% of the pigeonpea fields. Its average density was 4 cysts per 100 cc soil. Out of eight districts surveyed, Hoplolaimus was most prominent in Jalaun district with PV 491.9 followed by Mahoba with PV 288.5. Similarly, Tylenchorhynchus was most prominent in Kanpur district with PV 290 followed by Jalaun with PV 232.7. H. cajani was most prominent in Mahoba district with PV 17.7 followed by Jalaun and Kanpur districts.